Exchange rates and insulation in emerging markets. (Metro Manila, Philippines Asian Development Bank, 2017)
A number of recent theoretical and empirical studies cast doubt on the shock mitigating benefits of exchange rate flexibility. In this paper, the authors cite and expound on a 2017 study showing that flexible exchange rates promote output and financial stability in the face of global shocks. The authors argue that exchange rate flexibility does provide insulation, and there is less robust evidence that limited flexibility is enough to insulate emerging markets from shocks.
Keywords: Finance; Financial institutions; Electronic books